Awareness and Practice of Lymphedema Prevention among Women with Breast Cancer at Tertiary Cancer Hospital, Chitwan, Nepal - Ranabhat, Mina; Neupane, Sarmila; Koirala, Sushila (Journal of College of Medical Sciences-Nepal, 2025)
Background Breast Cancer Related lymphedema (BCRL) is the most common complication of breast cancer treatment. It can be prevented by early awareness of BCRL and its risk factors and continuing exercise after surgery and treatment. The objective of this study is to identify the awareness and practice of lymphedema prevention among women with Breast Cancer at Tertiary Cancer Hospital, Chitwan, Nepal. Methods Cross-sectional study design was used, with the sample of 115 breast cancer women who were attending at B.P.Koirala Memorial Cancer Hospital. A non-probability purposive sampling technique was used for sample selection. Data were collected between February 2024 to August 2024 using semi structured interview schedule after obtaining the ethical approval from Institutional Review Committee of B.P.Koirala Memorial Cancer Hospital (BPKMCH-IRC). Data were entered into IBM SPSS version 16. Data was analyzed using descriptive and inferential Statistical tools. p-value <0.05 was considered as Statistically significant. Results The study revealed that out of 115 respondents, only 20% demonstrated fair level of awareness and 73% displayed a fair level of practice towards awareness and prevention breast cancer related lymphedema. Regarding practice 77.3% had continue exercise of arm according to advice of health-persons. Level of awareness of lymphedema prevention is statistically significant with age (P=0.038) and family history (P=0.026). Conclusions The findings indicate that a substantial percentage of respondents possess a fair level of awareness and more than half have practice of prevention of lymph edema of arms. Therefore, the need for awareness programs concerning prevention of breast cancer related lymphedema.